+0  
 
+5
766
2
avatar

prove 

sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)
I tried to make it with no sucsess
Many thanks

Guest Feb 24, 2017

Best Answer 

 #2
avatar+19653 
+25

prove 
sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)

 

\(\begin{array}{|rcll|} \hline && \frac{\sec^2(x)\cdot \csc^2(x)}{\csc^2(x) - \sec^2(x)} \\ &=& \frac{1}{ \frac{\csc^2(x) - \sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{\csc^2(x)}{\sec^2(x)\cdot \csc^2(x)} -\frac{\sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{1}{\sec^2(x)} -\frac{1}{ \csc^2(x)} } \quad & | \quad \frac{1}{\sec(x)}=\cos(x) \quad \frac{1}{ \csc(x)}=\sin(x) \\ &=& \frac{1}{ \cos^2(x) - \sin^2(x) } \quad & | \quad \cos(2x) = \cos^2(x) - \sin^2(x) \\ &=& \frac{1}{ \cos(2x) } \quad & | \quad \frac{1}{\cos(x)}=\sec(x)\\ &=& \sec(2x) \\ \hline \end{array} \)

 

laugh

heureka  Feb 24, 2017
 #1
avatar+87333 
0

sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)    simplify the right side

 

(sec^2x*csc^2x)/ (csc^2x - sec^2x)   =

 

( 1/cos^2x * 1 / sin^2x)  / ( 1/sin^2x -  1/cos^2x)  =

 

Get a common denominator for the fractions in the denominator  = sin^2xcos^2x

 

[ 1/(cos^2x sin^2x)] / [ ( cos^2x - sin^2x) / ( sin^2x cos^2x) ]  =

 

Invert the fraction in the denominator and multiply by the numerator

 

[ 1/(cos^2x sin^2x) ] * (sin^2x cos^2x)  / [cos^2x - sin^2x]  =

 

1 / [ cos^2x  - sin^2x ] =

 

1/ cos2x    =

 

sec2x

 

 

 

cool cool cool

CPhill  Feb 24, 2017
 #2
avatar+19653 
+25
Best Answer

prove 
sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)

 

\(\begin{array}{|rcll|} \hline && \frac{\sec^2(x)\cdot \csc^2(x)}{\csc^2(x) - \sec^2(x)} \\ &=& \frac{1}{ \frac{\csc^2(x) - \sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{\csc^2(x)}{\sec^2(x)\cdot \csc^2(x)} -\frac{\sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{1}{\sec^2(x)} -\frac{1}{ \csc^2(x)} } \quad & | \quad \frac{1}{\sec(x)}=\cos(x) \quad \frac{1}{ \csc(x)}=\sin(x) \\ &=& \frac{1}{ \cos^2(x) - \sin^2(x) } \quad & | \quad \cos(2x) = \cos^2(x) - \sin^2(x) \\ &=& \frac{1}{ \cos(2x) } \quad & | \quad \frac{1}{\cos(x)}=\sec(x)\\ &=& \sec(2x) \\ \hline \end{array} \)

 

laugh

heureka  Feb 24, 2017

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.